The influence of islamic leadership and self efficacy on teacher performance with job satisfaction - Yulihardi, Yulihardi; Alhempi, R Rudi; Akmal, Akmal; Febriani, Rina; Afrida, Afrida; Shaddiq, Syahrial (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The influence of Islamic leadership and self-efficacy on teacher performance is a dynamic interplay that can significantly impact the quality of education. Leaders who embrace Islamic principles can create an environment that nurtures self-efficacy among teachers, leading to enhanced motivation, job satisfaction, and ultimately, improved student learning outcomes. This study aims to determine the effect of Islamic leadership and self-efficacy on teacher performance with job satisfaction as an intervening variable The research concept is a path analysis model used to analyze the pattern of relationships between variables to know the direct or indirect effect of the independent variable (exogenous) on the dependent variable (endogenous). The sample of this study was all teachers of SD IT and SMP IT Al-Kautsar Mukomuko as many as 81 teachers. The results of the analysis show that Islamic leadership has a significant positive effect on teacher performance. Self-efficacy has a significant positive effect on teacher performance. Job satisfaction has a significant positive effect on teacher performance; Islamic leadership has a significant positive effect on job satisfaction. The conclusion was job satisfaction mediates the influence of Islamic leadership on teacher performance